Impacts of acute exposure of industrial chemicals and pesticides on the survival of fish (Tilapia guineensis) and earthworms (Aporrectodea longa) - Doris F. Ogeleka; Emmanuel T. Ogbomida; Isioma Tongo; Alex A. Enuneku; Thomas O. Ikpesu; Lawrence I.N. Ezemonye (MDPI AG, 2016)
Ecotoxicological effects of industrial chemicals (Rig wash, Oil eater, Nalco, Glycol™) and pesticides (Propoxur, Deltamethrin, Atrazine, Furadan) on Tilapia guineensis (fish) and Aporrectodea longa (earthworms) were tested using the Organisation for Economic Cooperation and Development (OECD) # 203 and 207 protocols. The water and soil ratings indicate that the test chemicals were toxic to the organisms. The estimated 96 hour lethal concentration LC50 values for Rig wash, Oil eater, Nalco EC1304A/COT 505, Glycol, Propoxur, and Deltamethrin were 26.34±0.46, 6.02±0.30, 3.07±0.14, 1.31±0.01, 20.91±0 and 0.01±0 mg/l respectively. In the earthworm bioassay, the estimated 14-day LC50 values for Rigwash, Oil eater, Nalco EC1304A/COT 505, Glycol, Atrazine and Furadan were 80.05±3.5, 151.55±10.7, 172.63±14.2, 63.72±2.43, 4.97±0 and 0.29±0 mg/kg respectively. Safety factors are arbitrarily built in around the LC50 values in order to arrive at environmentally tolerable concentrations. The concentration of a chemical in the receiving environment should not exceed 10% of the L50. The organisms exposed to the test chemicals showed significant difference when compared with the levels measured in the control group. The observed sensitivity of the test organisms to the chemicals indicates that adherence to standard safety limits/measures should be maintained during use and disposal of hazardous chemicals. This would ensure that the biotic components of the Nigerian Niger Delta ecosystem are prudently protected.